José Rodrigues da Costa: um tipógrafo na Cidade da Parahyba (1848-1866) - Peixoto, Thayná Cavalcanti (2017)
From the printing- machines of the Typographia de José Rodrigues da Costa, provincial documents from the years 1848 to 1862 were printed successively, in addition to an average of 12 newspapers and six writings by authors from the province of Paraíba between 1848 and 1866. Due to this objective, this work has the objective of describing a trajectory of José Rodrigues da Costa, a major producer and disseminator of written culture in the capital of the Northern Paraíba Province, between 1848 and 1866 (the year of his death). Therefore, I´m considering José Rodrigues da Costa as an intermediary of the written culture, based on what Robert Darnton (2010) categorized as literary intermediaries: those who performed the activities of editors, typographers, printers, booksellers, etc., who were both responsible for the production as well as for the propagation of printed matter in their respective epochs. Linked to this, it is necessary to add the notions of political cultures and networks of sociability, to identify if the social relations established by the typographer influenced or not their permanence in the printing market in the capital. In this way, the research is based on a wide set of sources, composed mostly by newspapers and some of the writings printed in his workshop, and by the work of Eduardo Martins: A Tipografia do Beco da Misericórdia: apontamentos históricos (1978), which is a reference on the trajectory of the typographic establishment. Thus, it was possible to identify that the typographer was responsible for the production of several printed genres, and reached the top of his performance as an intermediary of the written culture, in my opinion, when he printed a newspaper of his property, O Publicador, which would become one of the most enduring newspapers of Paraíba in the imperial period.